"Minimal metabolism": A key concept to investigate the origins and nature of biological systems. (23rd August 2021) - Lauber, Nino; Flamm, Christoph; Ruiz‐Mirazo, Kepa
Abstract: The systems view on life and its emergence from complex chemistry has remarkably increased the scientific attention on metabolism in the last two decades. However, during this time there has not been much theoretical discussion on what constitutes a metabolism and what role it actually played in biogenesis. A critical and updated review on the topic is here offered, including some references to classical models from last century, but focusing more on current and future research. Metabolism is considered as intrinsically related to the living but not necessarily equivalent to it. More precisely, the idea of "minimal metabolism", in contrast to previous, top‐down conceptions, is formulated as a heuristic construct, halfway between chemistry and biology. Thus, rather than providing a complete or final characterization of metabolism, our aim is to encourage further investigations on it, particularly in the context of life's origin, for which some concrete methodological suggestions are provided. Also see the video abstract here: https://youtu.be/DP7VMKk2qpA Abstract : "Minimal metabolism" is conceived as the functional bootstrapping between a set of multiple transformation processes that synthesize a diversity of material constraints and the assorted control exerted on it by those constraints. Empirical research should thus focus on "one‐pot" chemistries, under non‐equilibrium heterogeneous conditions, concurrent with precursors of biological control mechanisms.